2017
DOI: 10.1261/rna.059220.116
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic stabilities of three-way junction nanomotifs in prohead RNA

Abstract: The thermodynamic stabilities of four natural prohead or packaging RNA (pRNA) three-way junction (3WJ) nanomotifs and seven phi29 pRNA 3WJ deletion mutant nanomotifs were investigated using UV optical melting on a three-component RNA system. Our data reveal that some pRNA 3WJs are more stable than the phi29 pRNA 3WJ. The stability of the 3WJ contributes to the unique self-assembly properties of pRNA. Thus, ultrastable pRNA 3WJ motifs suggest new scaffolds for pRNA-based nanotechnology. We present data demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…Relative to the phi29 3WJ, the M2 and SF5 3WJs have higher thermodynamic stabilities. [22] Our in vitro characterization of the 3WJs revealed that they have different thermal and serum stabilities (Table 1). The relationship between sequence and stability remains unclear, although the phi29 and M2 3WJs adopt distinct helical arrangements in solution [28] that may contribute to differences in stability.…”
Section: Chemistry-a European Journalmentioning
confidence: 96%
“…Relative to the phi29 3WJ, the M2 and SF5 3WJs have higher thermodynamic stabilities. [22] Our in vitro characterization of the 3WJs revealed that they have different thermal and serum stabilities (Table 1). The relationship between sequence and stability remains unclear, although the phi29 and M2 3WJs adopt distinct helical arrangements in solution [28] that may contribute to differences in stability.…”
Section: Chemistry-a European Journalmentioning
confidence: 96%
“…The 3WJ is an important contributor to pRNA self-assembly. Indeed, pRNA 3WJs have a wide range of thermodynamic stabilities [ 185 ]; exchanging an unstable 3WJ for a stable 3WJ can direct pRNA to self-assemble into larger multimers in vitro [ 184 , 186 ].…”
Section: Emerging Rna-based Technologiesmentioning
confidence: 99%
“…Specifically, it will be important for future studies to establish the pharmacokinetic/pharmacodynamic superiority of FA- or aptamer-3WJ-siRNA molecules over similar constructs lacking the 3WJ connector. Additionally, present engineering efforts are focused on the phi29 3WJ; phylogenetically related 3WJs with higher thermodynamic stabilities [ 185 ] may be better vectors for siRNA delivery. Moreover, in contrast to other synthetic RNAi triggers [ 200 ], it remains unclear how exactly chimeric 3WJ-siRNA molecules interface with the RNAi machinery to trigger gene silencing.…”
Section: Emerging Rna-based Technologiesmentioning
confidence: 99%
“…97,98 Recent work has narrowed engineering efforts to the unusually stable 3WJ motif found within the pRNA structure. [99][100][101] The phi29 pRNA 3WJ has been used to construct RNA polygons, 102-105 tetrahedra 106 (Fig. 4E), and prisms.…”
Section: Engineering Of Viral Prnamentioning
confidence: 99%
“…[108][109][110][111][112][113] To date, only the phi29 pRNA sequence has been developed for RNA nanotechnology. Related or engineered pRNA sequences with different thermodynamic, 100 conformational, 93 and selfassembly 91,92 properties may prove useful for tailoring the features of pRNA-based structures for specific applications.…”
Section: Engineering Of Viral Prnamentioning
confidence: 99%